Stability Analysis with Bifurcation of an SVIR Epidemic Model Involving Immigrants - Naji, Raid; Muhseen, Ahmed (Iraqi Journal of Science, 2024)
There are many factors effect on the spread of infectious disease or control it,some of these factors are (immigration and vaccination). The main objective of thispaper is to study the effect of those factors on the dynamical behavior of an SVIRmodel. It is assumed that the disease is spread by contact between members ofpopulations individuals. While the recovered individuals gain permanent immunityagainst the disease. The existence, uniqueness and boundedness of the solution ofthis model are investigated. The local and global dynamical behaviors of the modelare studied. The local bifurcations and Hopf bifurcation of the model areinvestigated. Finally, in order to confirm our obtained results and specify the effectsof model’s parameters on the dynamical behavior, numerical simulation of the SVIRmodel is performed.